US data on children and youth caregivers in amyotrophic lateral sclerosis. (7th April 2020) - Kavanaugh, Melinda S.; Cho, Chi C.; Howard, Megan; Fee, Dominic; Barkhaus, Paul E.
Abstract : Objective: An estimated 1.4 million young caregivers (<19 years of age) in the United States provide care to ill family members yet remain hidden from state and national caregiving programs and services, including amyotrophic lateral sclerosis (ALS) caregiving services. Given the intensive care needs and acuity of ALS, appreciation of the young caregiver experience within the family context may have a significant impact on patient and family quality of life. This article seeks to identify family and youth caregiver characteristics and perceptions of care through interviews with 38 youth caregivers and their families with ALS. Methods: Online adult surveys and follow-up youth interviews were conducted with families with ALS across the United States in this cross-sectional study. Participants were accessed through chapters of the ALS Association. Both thematic content analysis and descriptive statistics were used. Results: Youth caregivers (n = 38) ranged in age from 8 to 18 years and spent an average of 5 h/d providing care for an average of 12 tasks. Persons with ALS relied on youth primarily due to cost and identified complex feelings about relying on youth caregivers, including feeling like a failure, guilty, but proud. Conclusion: Youth are intricately involved in all areas of caregiving in ALS. They are isolated and have little training or guidance in care, yet they are able to identify ways to manage their care burden. Results provide clear implications for health care professionals in designing best care and support practices for persons with ALS and their young caregivers.